Pembelajaran Sejarah Lokal Gerakan Samin Surosentiko di SMA Negeri 1 Cepu - Naufal Nursyifa Rizki Widodo; Tsabit Azinar Ahmad (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Local history learning plays a strategic role in building students' historical awareness and cultural identity, but its formal integration into history lessons at SMA Negeri 1 Cepu has yet to materialize. This study aims to describe the planning, implementation, and evaluation of local history learning, the "Samin Surosentiko Movement," which is integrated into colonial history materials at SMA Negeri 1 Cepu. The study used a qualitative approach with a case study design. Data were collected through semi-structured interviews with history teachers, students, and the vice principal for curriculum, classroom observations, and documentation studies of curriculum tools and documents. These data were then analyzed using qualitative coding techniques. The results indicate that although local history learning has taken place contextually, communicatively, and meaningfully in the classroom, and has had a positive impact on student understanding, interest, and motivation, it has not been formally integrated into planning documents, learning tools, or evaluation systems. The inclusion of material still relies on teacher initiative and is not supported by written school policies or adequate teaching materials.